ANALISIS KESULITAN MEMBACA TEKS BACAAN PADA SISWA SMK KRISTEN IMMANUEL II - Setiany, Venny; Veronica, Tjen; Khiong, Bun Yan (Universitas Tanjungpura, 2025)
Reading is one of the most important components of Chinese language courses. Some people consider reading to be a difficult subject, especially for students who do not have a foundational knowledge of Chinese. During the learning process, they often encounter various difficulties. In order to identify the reasons behind students